How many plants feed the world? - Prescott-Allen, Robert; Prescott-Allen, Christine (1990)
FAO food supply data for 146 countries were analyzed to identify the plant commodities that account for the top 90% of each country's per capita supply of food plants by weighs calories, protein, and fat. The plant commodities were divided into two groups: species commodities, such as ?cabbages,? that can be attributed to particular species; and general commodities, such as ?hydrogenated oils,? whose species composition is not known. A total of 82 species commodities and 28 general commodities contribute 90% of national per capita supplies of food plants. The 82 species commodities consist of 103 species. Fifty-six of these commodities, comprising 75 species, individually account for 5% or more of at least one county's supply of a nutritional category (plant weight, plant calories, plant protein, plant fag. These figures are several times higher than previous findings that very few (7-30) plant species feed the world. The new figures are considered more accurate because they derive from national supply rather than global production data and from several separate measures of the importance of a food commodity rather than one. The results suggest that (1) plant species diversity remains a significant factor for world food supply; and (2) a conservation priority is to maintain both this wider away of species and the diversity of genetic variants that comprise each species.